On effective use of petroleum sources of energy - Аксьонов, О. Ф.; Бойченко, С. В.; Матвеева, О. Л. (Proceedings of National Aviation University (archive), 1998)
Considered is the problem of provision of national economy of Ukraine, especially aviation, with sources of energy of petroleum origin. Given is general characteristics of fuel and energy complex (FEC) in Ukraine. Main attention is concentrated on economic and ecological aspects of energy problems and the ways of their solutions. Substained is the necessity to carry out research in the efficiency of the use petroleum fuel consumption, introduction of new progressive technologies of storage, transportation, fuel transfer, also obligatory certification of petroleum products on their quality and ecology